A Study of Fourth Industrial Revolution on Management Accounting Profession - Obembe, Oluwabukunmi Eunice (Management Analytics and Social Insights, 2025)
The Fourth Industrial Revolution (4IR) marks a paradigm shift for industries' enterprises and professions. There will be a radical shift in nearly every facet of enterprises and professions. The recent industrial revolution has created technological upheaval, and the accounting profession is not immune to it. 4IR and the development of smart technology are changing how accountants typically accomplish their jobs. Therefore, a revision of the functions managers and accountants now play is required to account for the shift in the field's established practices, procedures, and ways of doing work. This study intends to update the skills necessary for upcoming management accounting graduates by reviewing the literature on the effects of 4IR on the management accounting profession and graduate preparedness for 4IR employment. The mismatch between talents and the necessary skills for long-term work contentment are two topics covered in previous research. The literature research makes it possible to determine the best ways for universities to address these problems. Higher education institutions stand to gain from the study as they include 4IR into their curriculum to generate graduates who are capable and prepared for the workforce.